(untitled) (Conferencea, 2023)
Waterproofing materials in structures and buildings are exposed to ultraviolet rays, temperature changes, oxygen and ozone in the air, wind force, precipitation in the form of rain and snow, microorganisms, aggressive liquid media and gases, mechanically contaminated pumps, stress and other external influences factors. As a result of these factors, waterproofing materials become unusable.